Study of Efficiency of Hydrogen-Fluorite (2HF) Gas Cleaning in Inertial Scrubber - Avazbek Khoshimov (European Science Publishing, 2023)
The article examines the physical and chemical properties of secondary gases coming out of chemical industry enterprises to the environment and solves the problems of gas disposal based on their scale. Secondary gas was selected for experiments and laboratory analyzes were performed. Based on the results obtained in the experiments, the optimal parameters of the device for different values of variable factors are based.
Keywords: aerosols, absorbent, hydrogen-fluoride gas, calcium technical white soda, calcium carbonate soda, technical shampoo.